Synergistic Antitumor Activity of Gramicidin/Lipophilic Bismuth Nanoparticles (BisBAL NPs) on Human Cervical Tumor Cells - Cabral-Romero, Claudio; García-Cuellar, Claudia María; Hernandez-Delgadillo, Rene; Sánchez-Pérez, Yesennia; Meester, Irene; Solís-Soto, Juan Manuel; Pineda-Aguilar, Nayely; Chellam, Shankararaman (Frontiers in Nanotechnology, 2021)
The objective of this study was to study the synergistic antitumor effect of lipophilic bismuth nanoparticles (BisBAL NPs) with the antibiotic solution Neo-Poly gramicidin on human cervical tumor cells. The effect of BisBAL NPs and Neo-Poly gramicidin solution on cervical cancer cell line (HeLa) was determined by the MTT cell viability assay and fluorescence microscopy. After a 24-h exposure to 0.1x Neo-Poly gramicidin HeLa cell growth decreased 94%. Fluorescence microscopy confirmed the antitumor effect cell death was higher among treated than among non-treated cells cells. Individually, gramicidin (0.04 mg/mL) inhibited HeLa tumor cell growth most (40%), and neomycin (0.04 mg/mL) least (21%). Gramicidin (0.3 mg/mL) in combination with different concentrations (1-150 µM) of BisBAL NPs had a synergistic antitumor effect against HeLA cells, reaching an < 86% tumor growth inhibition. As far as we know, we are the first to describe the antitumor activity of the antibiotic Neo-Poly gramicidin on a human cervical cancer cell line. The action mechanism of gramicidin/BisBAL NP is based on a strong damage on cell membrane and nucleous of tumor cells. A synergistic effect of gramicidin with BisBAL NPs may be useful as an alternative therapy for cervical cancer patients.